(untitled) (Revista Contexto & Saúde, 2026)
The objective of this study is to describe the validation and implementation of a checklist for intra-hospital transport of critically ill adult patients. The content of the checklist was validated by a panel of experts using the Delphi technique, followed by internal consistency analysis using Cronbach’s alpha. In addition, indicators were developed to monitor the intra-hospital transport of critically ill adult patients. The final version of the checklist included ten domains: patient identification, invasive devices, level of consciousness, hemodynamics, equipment, pre-transport monitoring, post-transport monitoring, complications, medications, and contrast. Four rounds were conducted for content validation, and an internal consistency index of 0.845 was obtained. Six indicators were developed, including one structure indicator, four process indicators, and one outcome indicator. The developed instrument was validated and demonstrated good internal consistency. The outcomes of the checklist implementation indicated good acceptance by the nursing team and support from service coordination, with emphasis on improved organization of intra-hospital transport processes. It is expected that its application will contribute to the prevention of adverse events during intra-hospital transport.